A Prospective Cohort Study of Metformin as an Adjuvant Therapy for Infertile Women With Endometrial Complex Hyperplasia/Complex Atypical Hyperplasia and Their Subsequent Assisted Reproductive Technology Outcomes - Kong, Wei-ya; Liu, Zheng-ai; Zhang, Na; Wu, Xue; Zhao, Xing-bo; Yan, Lei (Frontiers in Endocrinology, 2022)
Objective To investigate the adjuvant efficacy of metformin treatment to achieve pathological complete response (CR) in patients with endometrial complex hyperplasia (CH) and complex atypical hyperplasia (CAH), and secondarily, to evaluate their pregnancy outcomes after following assisted reproductive technology (ART). Study Design This prospective cohort study analyzed 219 patients diagnosed with infertility and CH/CAH from January 2016 to December 2020. Among these patients, 138 were assigned to the control group (progesterone alone) and 81 were assigned to the study group (progesterone+metformin). After 8/12 weeks of therapy, the treatment responses were assessed by histological examination of curettage specimens obtained by hysteroscopy. Once the pathological results indicated CR, the patients were able to receive ART. The ART treatment and follow-up data of these patients were collected and analyzed. Results 116 patients in the control group achieved CR, compared with 76 patients in the study group. The CR rate in the control group was significantly lower than that in the study group (P=0.034). We then divided the patients into subgroups to compare the treatment responses. In the subgroup analyses, patients with body mass index (BMI) ≥25 kg/m2 and patients with polycystic ovarian syndrome (PCOS) had higher CR rates in the metformin group compared with the control group (P=0.015, P=0.028 respectively). Subsequently, 68 patients in the control group and 47 patients in the study group received an ART cycle. We examined the pregnancy indications and found no significant differences in the clinical pregnancy rate and live birth rate between the two groups (P>0.05). Conclusion Regression of CH/CAH may be improved by progesterone+metformin compared with progesterone alone. The effect was particularly pronounced in patients with BMI ≥25 kg/m2 and patients with PCOS. Metformin had no obvious effect on subsequent ART outcomes. The trial is registered on the publicly accessible website: Clinical Trial Registration http://www.chictr.org.cn/showproj.aspx?proj=15372, identifier ChiCTR-ONR-16009078.